The Effectiveness and the Contribution of Regional Taxes for Regional Original Income in Ex-Karesidenan Madiun - Iwan Suhasto; Nova Widodo; Sundaru Wibowo (Politeknik Negeri Madiun, 2020)
The establishment and regional development require the availability of large funds; therefore, it is necessary to maximize the sources of regional acceptance. The region of East Java West that has a potential source of regional income that is quite a lot derived from regional tax funds that function to be able to further improve the system and mechanism of development of autonomous regions. The focus of this research is knowing the effectiveness and contribution of regional taxes on regional indigenous revenue. This research was conducted in the local government of the ex-karesidenan Madiun. The data used in this research is secondary data. Data is analysed quantitatively. The Data was analysed by using tax effectiveness analysis, analysis of tax contributions, and then classified based on the effectiveness and contribution of local taxes. The result of regional tax effectiveness assessment can be concluded that the regional tax effectiveness for three years shows maximum results with very effective criteria, because of the effect given to the targets that want to was declared more than 100%. Local tax contributions can be concluded that regional tax contributions to indigenous revenue in the Western East Java region for three years contributed to the criteria of 20%-30% of the regional original revenue. The highest regional tax in the year 2015 – 2017 is found by the Revenue Board of Kota Madiun. While the lowest level of regional tax contribution in 2015-2016 is on the local revenue board of Ngawi and in 2017 is on the Regional Revenue Board of Ponorogo.